A New Framework for Review Research from a Panoramic Perspective: Concepts, Processes and Demonstrations - Chen Hua (Zhishi guanli luntan, 2022)
[Purpose/significance] Panoramic backtracking integrates the thinking mode of panoramic analysis with the traditional methods of text analysis and document metrology and visualization technology, to achieve the expansion and innovation of the review research framework. [Method/process] Based on the analysis of concepts and basic attributes of panoramic backtracking, this paper constructed a new framework of five processes including data collection and delamination, diagnosis of time slices, analysis of dimensional model structure, hierarchical recursive visual situation presentation, and combined overall conclusion acquisition. The paper took the research on the performance appraisal of financial expenditure in China as an example for exploratory verification. [Result/conclusion] This paper proves that panoramic backtracking has comparative advantages in terms of diversification of data collection, refinement of the analysis process, standardization of the process design, and more comprehensive conclusion.